A 25 kW high temperature electrolysis facility for flexible hydrogen production and system integration studies. (11th June 2020) - O'Brien, J.E.; Hartvigsen, J.L.; Boardman, R.D.; Hartvigsen, J.J.; Larsen, D.; Elangovan, S.
Abstract: A 25 kW high-temperature electrolysis (HTE) flexible test facility has been developed at Idaho National Laboratory (INL) for performance evaluation of solid-oxide electrolysis cell (SOEC) stacks operating independently or in thermal integration with co-located systems. This facility is aimed at advancing the state of the art of HTE technology while demonstrating dynamic grid and thermal energy integration and operational characteristics. The 25 kW HTE flexible test station will provide a test bed for state-of-the-art HTE stack technologies from multiple industry partners. The test station will ultimately be integrated with a co-located thermal energy distribution and storage system within the INL Systems Integration Laboratory. The HTE test station will also be designed to communicate with co-located digital real-time simulators for dynamic performance evaluation and hardware-in-the-loop simulations in a dynamic microgrid environment. Operation of the 25 kW HTE system will be followed by deployment of a test skid with infrastructure support for up to 250 kW HTE turnkey systems. A detailed description of the 25 kW HTE system is provided along with results obtained from initial stack testing at the 5 kW scale. Highlights: A 25 kW high-temperature electrolysis research facility has been established. The facility will be operated in an integrated energy system environment. Initial operation of the HTE facility has been completed at the 5 kW scale. Solid oxide stacks have matched thermal expansion interconnects and cells. The stacks are hermetic due to the use of glass seals.